Editorial: Inclusive Media Literacy Education for Diverse Societies - Bozdağ, Çiğdem (2022)
This editorial introduces the thematic issue titled Inclusive Media Literacy Education for Diverse Societies. We start by introducing our aims for developing a more open and inviting approach to media education. We argue for a media education that acknowledges a variety of voices, and that provides skills and recognition for everyone, irrespective of their social class, status, gender identification, sexuality, race, ability, and other variables. The articles in this issue address the role of media literacy education in relation to questions of in- and exclusion, social justice, voice, and listening. The issue covers a variety of critical, non-Western perspectives needed to challenge dominant regimes of representation. The editorial is enriched by the artist Neetje’s illustrations of the workshop that preceded the publication of this thematic issue.